Chaetopsina aquatica sp. nov. (Hypocreales, Nectriaceae) from the River Nile, Egypt - Bakhit, Mahmoud S.; Abdel-Aziz, Ahmed E. (Phytotaxa, 2021)
A new species, Chaetopsina aquatica, collected from the River Nile, Sohag, Egypt, is described and illustrated. Phylogenetic analyses of the combined ITS and LSU rDNA placed the new species within Chaetopsina as a phylogenetically distinct species. Chaetopsina aquatica formed a basal clade to a node containing C. aurantisalinicola and C. penicillata. The new species is characterized by its longer conidia (20–35.2 × 5–8.5 μm on natural substrate, 27.5–41.5 × 5–7 μm in culture) than those reported in Chaetopsina species.